Life as a “Part-Time” Scientist - Ambily Banerjee (Opticon1826, 2007)
Within the Faculty of Life Sciences, I am yet to encounter a part-time researcher. Why has this species never successfully evolved within the ecosystem that we call academia? When I returned to work eighteen months ago after my maternity break, I was offered the option of working part-time, as the law demands. I chose to try it out for a month, working three days a week. During this time, I realised two things: I had to rely heavily on my colleagues to cover for me on the days I was off, and my project moved ahead at a grindingly slow pace. Neither of these scenarios was acceptable to me. As someone who had dedicated three years of hard work towards obtaining a Ph.D. I couldn’t envisage throwing away a rewarding career in favour of full time motherhood. But my family was also my first priority. So, like many working mothers I came up with a compromise. My day starts at 5am, and I work my full time hours by 3pm. Although some people still class me as a part-timer, as I am normally leaving work by the time they come back from lunch, I am happier that I get a few quality hours with my child everyday.